2015
DOI: 10.4172/1204-5357.1000123
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Intention to Adopt Internet Banking by Postgraduate Students of the University of Ibadan, Nigeria

Abstract: This study examines the factors influencing intention to adopt internet banking by postgraduate students of the University of Ibadan Nigeria. The study adopted the Technology Acceptance Model and Theory of Planned Behaviour as the theoretical framework. The survey instrument employed involved design and administration of a total of 522 survey questionnaires within the University. The results of the study reveal no significant relationship between demographic characteristics of the students and intention to ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 51 publications
3
11
0
Order By: Relevance
“…Online banking has contributed massively to the modernisation of banking services which has transformed from a traditional banking channel to a digital channel. Online banking services such as balance enquiry, printing statements, fund transfers to other accounts and bill payments are becoming famous nowadays (Fo & Ak, 2015). The study conducted by Islam et al (2019b) in Bangladesh on electronic banking found that banking, like other sectors, has passed through many transformations from traditional banking to online banking.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Online banking has contributed massively to the modernisation of banking services which has transformed from a traditional banking channel to a digital channel. Online banking services such as balance enquiry, printing statements, fund transfers to other accounts and bill payments are becoming famous nowadays (Fo & Ak, 2015). The study conducted by Islam et al (2019b) in Bangladesh on electronic banking found that banking, like other sectors, has passed through many transformations from traditional banking to online banking.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many of the previous studies have examined this variable as the most effective predictor of customer satisfaction because consumers rate their satisfaction based on the usefulness and power of an information system. A number of literatures find that perceived usefulness has a significant effect on intention to use ((Tun-Pin et al, 2019); (Putra & Baridwan, 2020); (Omotayo & Adebayo, 2015)  H_1 ∶ There is a significant effect of perceived usefulness on the intention to use peer-to-peer lending applications.…”
Section: Research Hypothesismentioning
confidence: 99%
“…It is explained that the ease of use of the nature of an innovation will directly affect the acceptance of the innovation (Fang, Chan, Brzezinski, & Xu, 2005). Additionally, simple, easy and user-friendly innovations such as the clarity of command and steps, simple content and visible graphical layouts significantly enhance the ease of use of the innovation and contribute in encouraging the adoption (Fo & Ak, 2015). Numerous researches proofed that the perceived ease of use of an innovation directly influences the acceptance and adoption towards internet banking.…”
Section: Perceived Ease Of Usementioning
confidence: 99%
“…There are various researches and studies that have identified that social norms played a vital role in affecting the adoption of internet banking. The results of the study conducted by Fo and Ak (2015) in Nigeria has indicated that the subjective norms factor is positively affecting the adoption of Internet banking by customers.…”
Section: Subjective Normsmentioning
confidence: 99%
See 1 more Smart Citation